Gelatin-based anticancer drug delivery nanosystems: A mini review - Jiang, Xianchao; Du, Zhen; Zhang, Xinran; Zaman, Fakhar; Song, Zihao; Guan, Yuepeng; Yu, Tengfei; Huang, Yaqin (Frontiers in Bioengineering and Biotechnology, 2023)
Drug delivery nanosystems (DDnS) is widely developed recently. Gelatin is a high-potential biomaterial originated from natural resources for anticancer DDnS, which can effectively improve the utilization of anticancer drugs and reduce side effects. The hydrophilic, amphoteric behavior and sol-gel transition of gelatin can be used to fulfill various requirements of anticancer DDnS. Additionally, the high number of multifunctional groups on the surface of gelatin provides the possibility of crosslinking and further modifications. In this review, we focus on the properties of gelatin and briefly elaborate the correlation between the properties and anticancer DDnS. Furthermore, we discuss the applications of gelatin-based DDnS in various cancer treatments. Overall, we have summarized the excellent properties of gelatin and correlated with DDnS to provide a manual for the design of gelatin-based materials for DDnS.